Analisis performa inkubator grashof dengan menggunakan lampu LED sebagai pemanas - Putra, R.O.; Tarigan, B.V.; Jasron, J.U. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2024)
The high infant mortality rate that occurs between the time after the baby's birth and the time when the baby is not exactly one year old is due to hypothermia/hypertermia, insufficient access to doctors and inability to pay for the use of pre-natal care equipment. Research has been conducted on the analysis of the performance of grashof incubators using LED lamps and copper fiber as heaters to determine the efficiency of LED lights when used for heating in a baby incubator (grazhof inkubator). The results of the research show that 20 watt LED lamp with the addition of fibre as a medium for the heating of air inside incubators is more efficient in tempering the air to reach a temperature of 35oC compared to a 25 watt fiber lamp that does not use a heater fiber. Temperature testing in a baby incubator is measured using a K-type thermocouple due to good accuracy and high sensitivity to temperature changes that need to be monitored in real time. From the results of the analysis of energy efficiency and heating speed (free convection) obtained results that show that with the addition of copper syrup as a heating medium in the incubator has a real influence on the speed of heating air inside the incubators.